Pengaruh Financial Cost dan Comprehensive Income terhadap Non-Interest Bearing Debt Perusahaan Badan Usaha Milik Negara (BUMN) Jasa Perbankan PT Bank Rakyat Indonesia (Persero) Tbk. - T Akmal Kurniawan; Friedel Tambunan; Frans A.C.H Simarmata (Akuntansi Prima, 2023)
The research was conducted to comprehensively determine the effect of non-interest bearing debt on financial cost and Comprehensive Income. This study uses a quantitative descriptive approach, with a population of SOEs engaged in financial services represented by PT Bank Rakyat Indonesia (Persero) Tbk. from several banks in Indonesia. The sampling technique uses a probability sample with a purposive sampling method. In addition, the sample data from this company were 20 from the last five years of PT Bank Rakyat Indonesia (Persero) Tbk's financial reporting. which includes Q1, Q2, Q3, and Q4 (Audited). Data analysis using SmartPLS4 software with the study results showed that the non-interest bearing debt variable significantly affects Comprehensive Income, and financial cost significantly affect Comprehensive Income. However, other factors affect the value of Comprehensive Income, which tends to increase, like pro forma profit. Thus H1, H2, and H3 are accepted, which means that there is a significant influence between non-interest bearing debt, earnings before tax, and Comprehensive Income.